The research on automatic seat control system model on automotive - Nguyễn Văn Thình (Journal of Technical Education Science, 2019)
This article discusses the research on operation and programming of microprocessor control in the car seat. Designing and manufacturing the model of electronic chair system for teaching. A deeper understanding of the operation of the system in particular and of the automobile in general. Nowadays, the control system of electronic chairs also has other functions such as location memory, lift up or lower the cushion height of the seats, simultaneous control of seats and rearview mirror, seatbelts adjustment, etc. All functions above are designed to increase the convenience and comfort for the car driver.